Pengaruh Health Coaching pada Self Help Group terhadap Efikasi Diri dan Kepatuhan Program Pengobatan Pasien Tuberkulosis Paru di Kota Sukabumi - Dedi Wahyudin; Nana Supriyatna; Sigit Mulyono (FORIKES, 2021)
World Health Organitazion (WHO) states that 9 million people suffer from TB every year. Even though every pulmonary TB patients would be face a long treatment time, negative community stigma, many drug side effects that make pulmonary TB sufferers prone to experiencing decreased self-efficacy and non-compliance with treatment program. This study aims to determine the effect of health coaching on self-help groups on self-efficacy and adherence to the treatment program for pulmonary TB patients in Sukabumi City. The research design was a quasi-experimental pre and post control group consisting of 18 respondents in the intervention group and 18 respondents in the control group who were not given intervention. The results showed that after health coaching was carried out in the self-help group in the intervention group, almost all respondents had high self-efficacy (95%) and were adherent to the treatment program (90%), while in the control group almost half of the respondents still had low self-efficacy (55%) and not adhering to the treatment program (40%), the results of statistical tests found that there was a difference in the effect of health coaching in the self-help group on self-efficacy and adherence to the treatment program for pulmonary TB patients who were given health coaching intervention in the self-help group and those who were not given intervention in the City Sukabumi (p value = 0.000). Recommended that service institutions provide health coaching to self-help groups as an additional intervention for pulmonary TB patients in order to maintain self-efficacy and adherence to the treatment program during treatment. Keywords: health coachin; self help group; self efficacy; treatment program adherence ABSTRAK World Health Organization (WHO) menyebutkan 9 juta orang terkena TBC setiap tahunnya. Padahal setiap pasien Tuberkulosis paru akan menghadapi waktu pengobatan yang cukup lama, stigma negatif masyarakat, efek samping obat yang banyak mengakibatkan penderita Tuberkulosis paru rawan mengalami penurunan efikasi diri dan ketidakpatuhan terhadap program pengobatannya. Penelitian ini bertujuan mengetahui pengaruh health coaching pada self help group terhadap efikasi diri dan kepatuhan program pengobatan pasien Tuberkulosis paru di Kota Sukabumi. Desain penelitian ini adalah quasi eksperimen dengan pendekatan pre and post with control group terdiri dari 20 responden kelompok intervensi dan 20 responden kelompok kontrol tidak diberikan intervensi. Hasil penelitian menunjukkan setelah dilakukan health coaching pada self help group pada kelompok intervensi hampir seluruhnya responden memiliki efikasi diri tinggi (95%) dan patuh terhadap program pengobatan (90%), sedangkan pada kelompok kontrol hampir setengahnya responden masih efikasi dirirendah (55%) dan tidak patuh terhadap program pengobatan (40%), Hasil uji statistic didapat ada perbedaan pengaruh health coaching pada self help group terhadap efikasi diri dan kepatuhan program pengobatan pasien Tuberkulosis paru yang diberikan intervensi health coaching pada self help group dan yang tidak diberikan intervensi di Kota Sukabumi (p value 0,000). Disarankan pada intitusi pelayanan agar dapat memberikan health coaching pada self help group sebagai intervensi tambahan pada penderita Tuberkulosis paru agar tetap terjaga efikasi diri dan kepatuhan terhadap program pengobatannya selama menjalani pengobatan. Kata kunci: health coaching; self help group; efikasi diri; kepatuhan program pengobatan